The Separation of the Restrictive Pronoun with Innama between Ibn Malik and Abu Hayyan - Assaedi, Saud Bin Obaidullah Bin Abid (Arts for Linguistic & Literary Studies, 2025)
This study investigates the grammatical issue of separating a pronoun restricted by innama, with particular focus on the debate between Ibn Malik and Abu Hayyan and its connection to Sibawayh’s position. Employing a detailed analysis of six thematic sections, the research traces the origins of the disagreement, reviews the views of grammarians who attributed the construction to poetic necessity, examines the contributions of al-Zajjaj, and analyzes both Ibn Malik’s interpretation and Abu Hayyan’s objections along with the responses to them. The findings indicate that grammarians often use the phrase “the pronoun after innama” as shorthand for “the pronoun restricted by innama,” and that the rules of separation apply equally to nominative and accusative pronouns. The study further concludes that the central point of contention stems from the ambiguity surrounding Sibawayh’s citation of the poetic line “innama nuqtalu iyyana,” which generated divergent interpretations of his intent. By uncovering the reasons for this ambiguity, the research clarifies the broader implications of pronoun restriction and its treatment in Arabic grammatical thought.